Morphological Variation between Hatchery Bred and Wild Caught Anabas testudineus in Malaysia - Okomoda Victor Tosin; Ahmad Azfar Mohamed; Nur Asma Ariffin; Ahmed Jalal Khan Chowdhury; Abol-Munafi Ambok Bolong (Tropical Life Sciences Research, 2022)
This study was designed to characterise the cultured and wild populations of Anabas testudineus in Malaysia using morphological parameters. Fish samples from the East and West coast of the country were obtained from fishermen (wild samples) and well-recognised climbing perch farmers in Kedah, Kelantan, Johor and Selangor. The Truss network method was applied to obtain necessary data and analysed to examine phenotypic variation between the cultured and wild stocks. Results obtained suggest that each hatchery population belonged to a distinct stock as revealed by their separate clustering into individual unique groups. However, an extensive overlap was observed in the wild population suggesting similarity of origin. The most important morphological parameters for the discrimination of the two populations are the homologous landmark B (i.e., snout to insertion of the pelvic fin) and C (i.e., above the eye to insertion of the pelvic fin). Genetic characterisation of the A. testudineus is needed to complement the findings of this study and establish a baseline for the development of a selective breeding programme for the fish species in Malaysia. Kajian ini dijalankan untuk mencirikan populasi Anabas testudineus yang dikultur dan liar di Malaysia menggunakan parameter morfologi. Sampel ikan dari pantai timur dan barat negara ini diperoleh daripada nelayan (sampel liar) dan penternak ikan yang diiktiraf di Kedah, Kelantan, Johor dan Selangor. Kaedah rangkaian Truss digunakan untuk mendapatkan data yang diperlukan dan dianalisis untuk memeriksa variasi fenotip antara stok kultur dan liar. Keputusan yang diperoleh menunjukkan bahawa setiap populasi penetasan tergolong dalam stok yang berbeza seperti yang didedahkan oleh kelompok berasingan ke dalam kumpulan unik individu. Walau bagaimanapun, pertindihan yang luas diperhatikan dalam populasi liar yang mencadangkan persamaan asal. Parameter morfologi yang paling penting untuk diskriminasi kedua-dua populasi ialah mercu tanda homolog B (iaitu, snout untuk memasukkan sirip pelvis) dan C (iaitu, di atas mata untuk memasukkan sirip pelvis). Pencirian genetik A. testudineus diperlukan untuk melengkapkan penemuan kajian ini dan mewujudkan asas untuk pembangunan program pembiakan terpilih untuk spesies ikan di Malaysia.